Adolescent at risk and prevention stigma from hadith perspective - Muhammad Arif Yahya,; Nurul Aqilah Mohamad Asri,; Zaizul Ab Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Social support is an important factor for a successful intervention process. The social community can assist in preventing adolescents from engaging in risky behaviour and charged with a crime or committing recurring offenses in the case of a relapse or recidivism. The threat of stigma must be addressed and reduced in the social community to protect the psychosocial wellbeing of at-risk adolescents. This qualitative study aimed to examine the significance of minimizing stigma against at-risk adolescents based on the hadith. Secondary data sources, such as articles, papers, symposia, and theses, were combined with primary sources, such as hadith scriptures and relevant lectures, to create a data set for the document analysis. Findings indicate that the hadith contains advice on how to avoid stigmatizing former offenders. The hazards of stigma and effective measures to counteract against it were extensively explored by Islamic thinkers. Consequently, this study examined a strategy for preventing stigma in the hadith to be utilized as a technique specified in the intervention and integration process involving at-risk adolescents. This study anticipates that stigma prevention strategies applied to at-risk adolescents based on the Hadis perspective can enhance their psychosocial wellbeing and enlighten intervention techniques for managing these adolescents.